2016
DOI: 10.2147/idr.s114770
|View full text |Cite
|
Sign up to set email alerts
|

Lyme disease: the promise of Big Data, companion diagnostics and precision medicine

Abstract: Lyme disease caused by the spirochete Borrelia burgdorferi has become a major worldwide epidemic. Recent studies based on Big Data registries show that >300,000 people are diagnosed with Lyme disease each year in the USA, and up to two-thirds of individuals infected with B. burgdorferi will fail conventional 30-year-old antibiotic therapy for Lyme disease. In addition, animal and human evidence suggests that sexual transmission of the Lyme spirochete may occur. Improved companion diagnostic tests for Lyme dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Linear regression of data from all included studies is shown in Figure 9, which demonstrates an increase in test sensitivity of 4% points over the 20-year study period. These results lend support to the recently published conclusion of Stricker and Johnson14 to the effect that “FDA-cleared commercial serological testing for Lyme disease is inadequate for the diagnosis of the disease”.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Linear regression of data from all included studies is shown in Figure 9, which demonstrates an increase in test sensitivity of 4% points over the 20-year study period. These results lend support to the recently published conclusion of Stricker and Johnson14 to the effect that “FDA-cleared commercial serological testing for Lyme disease is inadequate for the diagnosis of the disease”.…”
Section: Resultssupporting
confidence: 80%
“…Guidelines for IgM tests usually require that two or more bands are positive; however, a modified MiQ 12 2000 standard for Germany required only one IgM band for a positive diagnosis 13. There have been attempts to standardize bands and proposals to increase the sensitivity 14. Another adaptation of the technology uses antigens that are printed in strips on the polymer substrates, which are then reacted with patient serum and are more easily read manually or using a scanning densitometer.…”
Section: Test Methods For Detection Of Borrelia Infectionsmentioning
confidence: 99%
“…Epidemiological studies have shown that the incidence of Lyme disease (2–4), syphilis (5–7), and leptospirosis (8, 9) have increased, both within United States and globally (10, 11). However, the immunopathogenesis of spirochetal diseases remains unclear (12–14).…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of more effective therapy, health care organizations and insurers have become complacent about inadequate treatment for Lyme disease. 6 , 8 …”
mentioning
confidence: 99%
“…Because a safe and effective Lyme disease vaccine is presently out of reach for technical reasons, 28 , 29 we need targeted designer drugs to treat the Lyme spirochete, and we can use the HIV and HCV models to develop these drugs. 8 Designer drugs would avoid the overuse of 60-year-old antibiotics that are marginally effective to begin with, and targeted therapy would provide more rational treatment for the tick-borne disease. Development of designer drugs for Borrelia would also open the door for research into more effective treatment for tick-borne bacterial, protozoal, and viral coinfections.…”
mentioning
confidence: 99%